Early and late developmental arrest as complementary embryonic bet‐hedging strategies in African killifish. (22nd January 2015) - Pinceel, Tom; Vanschoenwinkel, Bram; Deckers, Pieter; Grégoir, Arnout; Ver Eecke, Tom; Brendonck, Luc
<x xml:space="preserve">Abstract</x> The production of dormant eggs is a crucial adaptation for African killifish of the genus Nothobranchius to survive in temporary waters. These habitats are often characterized by unpredictable variation in the suitability of growing seasons as a result of variable lengths of inundations and temporary colonization by piscivorous fish. Incomplete hatching could enable killifish to buffer against reproductive failure during unsuitable inundations. Although this phenomenon has been tentatively linked to variation in dormancy states, it has never been investigated under controlled conditions and its viability as a bet hedging strategy to distribute offspring over several inundations remains unclear. In the present study, we used common garden experiments to assess the contribution of environmental modulation and bet hedging to delayed hatching in Nothobranchius killifish by testing the feasibility of arrested development in the presence and absence of environmental cues. Overall, the results confirmed that the presence of cues signalling a threat (predator kairomones) inhibited hatching. However, delayed development also occurred independent of cues and was regulated at two stages. Developmental arrest in energy‐efficient dormancy stages could present a means for long‐term bet hedging over years, whereas arrest in the energy‐consuming final stage may serve a similar purpose over shorter time scales. © 2015 The Linnean Society of London, Biological Journal of the Linnean Society, 2015, 114, 941–948.